IT GRC Maturity on Organizational Performance and Financial Reporting Quality: A Systematic Review - Samsul, Sakia Putri; Muchran, Muchriana; Ramly, Ramly (West Science Interdisciplinary Studies, 2025)
This systematic literature review synthesizes extant research to elucidate the relationship between Information Technology Governance, Risk, and Compliance (IT GRC) maturity and its impacts on organizational performance and financial reporting quality. Guided by the PRISMA framework, the review analyzes 22 publications from 2021–2025. The findings reveal that IT GRC maturity significantly enhances organizational performance, primarily mediated through improved internal control effectiveness and strategic alignment, leading to superior financial and operational outcomes. Furthermore, it directly elevates financial reporting quality by mitigating material weaknesses and constraining earnings management, thereby strengthening financial integrity. The synthesis constructs an integrated framework demonstrating that mature IT GRC acts as a critical socio-technical determinant, translating governance structures into tangible value. However, the review identifies that these benefits are contingent upon overcoming integration challenges related to strategic alignment and human capital. The study concludes by recommending a holistic approach that synchronizes technology, processes, and skilled personnel, and highlights key avenues for future empirical research to further delineate these complex relationships.
Keywords: IT GRC Maturity; Organizational Performance; Financial Reporting Quality; Internal Control; Strategic Alignment